Co-Creation of Navigational Spaces When Facilitating Children’s Play - Oen, Marion (Nordic Journal of Comparative and International Education (NJCIE), 2023)
Facilitating children’s play is an important but potentially frustrating task for teachers in the field of Early Childhood Education and Care. Play is often understood as essential for children, and frequently being excluded from play is often experienced as problematic; Still, teachers are often uncertain about how to do play and there is a growing concern about the disappearance of play. This study aims to explore and identify navigational spaces for teachers to exercise agency when facilitating children’s play, and this article presents the co-creation of four such spaces. The co-creation has been done through a series of workshops and play initiations over six months, explored by ECEC teachers in conjunction with the author. The workshops are anchored in critical theory, and the idea is that the participants enrich the project through their various forms of expertise. Abductive analysis through workshops and a thematic analysis of sound and video recordings of these events shows the co-creation of the navigational spaces of framing, conditioning, timing, and knowledging to be central. To be able to co-create these navigational spaces, the repeated collective questioning and knowledge contributions of teachers and the researcher seem to be a central factor. By critically considering and exploring co-creational possibilities both the researcher and the teachers extended their play-facilitating repertoire and made the play-facilitating efforts increasingly explicit. This suggests that it is possible to simultaneously develop practice and scientific knowledge if interactions between the education sector and academia are facilitated. These insights will be beneficial for further investigations and innovations.